Effect of sulfuric acid hydrolysis on the structure and Pickering emulsifying capacity of acorn starch - Changsheng Guo; Sheng Geng; Yuzhong Shi; Chao Yuan; Benguo Liu (Food Chemistry: X, 2024)
The acid-hydrolyzed acorn starch samples (HAS-1, HAS-2, HAS-3, and HAS-4) were prepared from natural acorn starch (NAS) at sulfuric acid concentrations of 1, 2, 3, and 4 mol/L for 2 d. The particle characteristics and structures of HAS were investigated, and Pickering high internal phase emulsions (HIPEs) based on HAS were constructed and characterized. The results showed that with an increase in sulfuric acid concentration, the size, yield, amylose content, molecular weight, and amylopectin chain length of HAS gradually decreased. HAS retained an A-type crystal structure, and its relative crystallinity and short-range order degree gradually increased with increasing sulfuric acid concentration. Acid hydrolysis treatment improved the wettability of NAS, and its effect was positively correlated with the sulfuric acid concentration. HAS-3 and HAS-4 could stabilize the Pickering HIPEs with an oil phase volume fraction of 80% at c ≥ 1.5%. The mechanical properties of the HIPEs were positively correlated with c.